40 Years of Ancient TL - Sutton, S.; Bailiff, I.; Miallier, D.; Duller, G.; DeWitt, R. (Ancient TL, 2017)
The first issue of Ancient TL was published in September 1977, 40 years ago. The journal was started by the late David Zimmerman at Washington University in Missouri (USA) as an informal newsletter for thermoluminescence practitioners. Since then editors Steve Sutton (then Washington University; editor until 1984), Ian Bailiff (Durham, UK; 1984–1994), Didier Miallier (Clermont-Ferrand, France; 1995–2004), Geoff Duller (Aberystwyth, UK; 2004–2014) and Regina DeWitt (Greenville, NC, USA; since 2015) have continued the tradition and continually modernized the journal. Despite many changes the scope of the journal has been and still is to provide the luminescence and ESR community with ideas and essential information for laboratory work and serve as an outlet for community news.